Perancangan mesin penghancur sekam padi dengan poros penggerak horisontal - Ahmad Suudi; Novri Tanti; Jamiatul Akmal; Zulhendri Hasymi; Prasetyo Budiyanto (Jurnal Teknik Mesin Indonesia, 2019)
Husk is a waste from the grinding process with the characteristics of a hard, scaly and dry layer. In the rice milling process, according to the Agricultural Research and Development Agency, the Department of Agriculture obtained 20-30% of rice husk, 8-12% of bran and 50 - 63.5% of milled rice. It can be seen that the amount of waste produced is predominantly dominated by rice husk and if not handled it will be a problem for the environment. One effort to reduce the form of waste was carried out research design of rice husk grinding machine become powder. The implementation method starts with designing, manufacturing and testing. The design of the grinding machine is planned to use a fuel motor drive, the transmission uses a V belt and the type of grinder is a combination of discmill and hammermill.The results of research and design obtained rice husk grinding machine with specifications dimensions of 1100 mm high, 400 mm long and 500 mm wide, Hyundai gasoline engine drive HDE 390 with power 7.6 kW, elbow profile frame 50 mm x 50 mm, belt transmission and pulley with a ratio of 1: 1, a combination milling mechanism namely hammer mills which have 3 single hammer attrition mills and a front through grinder with the help of screw conveyor components. The test results of the grinding machine capacity obtained a production capacity of 10 kg / hour, and fuel consumption which is 2.162 liters / hour.